Effects of bolus injection rate on the pharmacodynamics and pharmacokinetics of propofol, etomidate and sufentanil in rats - Liu, Sicheng; Gong, Deying; Li, Xiaoxiao; Qiu, Feng; Zhang, Wensheng (Frontiers in Veterinary Science, 2025)
IntroductionThe preclinical phase of innovative drug research and development involves a comprehensive assessment of multiple variables that may influence therapeutic outcomes and safety profiles. Although injection rate represents a potentially modifiable parameter in pharmacological studies, its specific effects on experimental outcomes remain insufficiently characterized in animal models. This study systematically explored the relationship between the intravenous injection rates of three anesthetics and their pharmacodynamic and pharmacokinetic responses in rats.MethodsThree anesthetics were administered to rats via intravenous bolus at varying rates: fast (0.06 mL/s), medium (0.02 mL/s), and slow (0.01 mL/s). Quantitative behavioral assessments were conducted to determine onset latency and duration of anesthesia. Comprehensive safety evaluations included invasive hemodynamic monitoring, respiratory frequency measurements, and myoclonus scoring. Pharmacokinetic profiling was performed using plasma samples analyzed by validated HPLC and HPLC-MS techniques.ResultsFaster injection significantly altered pharmacodynamic profiles, with the fast group showing shorter onset latency and longer duration of effect compared to the slow group. However, this kinetic advantage was associated with a higher incidence of adverse events, including transient hypotension, increased respiratory depression, and more severe myoclonus. Pharmacokinetic analyses revealed dose-rate-dependent plasma concentration profiles, with Cmax values in the fast group significantly higher than those in the medium and slow groups.DiscussionThese findings demonstrate that injection rate directly influences both therapeutic and adverse effects through alterations in pharmacokinetic parameters, particularly Cmax. Setting a reasonable injection rate in animal experiments will show positive significance and help reduce related safety risks, especially in the application of anesthetics. In addition, strategically optimizing the injection rate during the development of innovative drugs is expected to improve the predictive validity of translational research.